Faktor Yang Mempengaruhi Loyalitas Pelanggan Pada Bengkel Abun Motor Palembang - Alexander, Martin; Artina, Nyimas (MDP Student Conference, 2024)
The purpose of this study is to determine the effect of price and quality of customer loyalty services in Abun Motor Palembang workshop. Data collection for this study distributed questionnaires to 200 respondents. Sampling using nonprobability sampling with purpsosve sampling method with the help of SPSS 23. The partial test results show that price and service quality have a significant positive effect on customer loyalty with a value of 0.000 < 0.05. Simultaneous tests prove that the F value is 119,255 with 0.000 significant values which means that price variables and service quality can be said to have a positive effect and significance on customer loyalty.